Bears of North America - Tekiela, Stan (Adventure Publications, an imprint of AdventureKeen, 2023)
"Get to know Black Bears, Brown Bears, and Polar Bears like never before-through Stan Tekiela's wildlife photography, personal anecdotes, and years of research. They are icons of our wild places. They are powerful and intimidating, yet they signify calmness, comfort, and peace. Bears are adored around the world. They are magnificent animals that capture our fascination. Enter the world of bears with award-winning author, naturalist, and wildlife photographer Stan Tekiela"--